The “Skinny” on brown fat, obesity, and bone - Devlin, Maureen J. (Inventions, 2015)
The discovery that metabolically active brown fat is present in humans throughout ontogeny raises new questions about the interactions between thermoregulatory, metabolic, and skeletal homeostasis. Brown adipose tissue (BAT) is distinct from white adipose tissue (WAT) for its ability to burn, rather than store, energy. BAT uniquely expresses uncoupling protein‐1 (abbreviated as UCP1), which diverts the energy produced by cellular respiration to generate heat. While BAT is found in small mammals, hibernators, and newborns, this depot was thought to regress in humans during early postnatal life. Recent studies revealed that human BAT remains metabolically active throughout childhood and even in adulthood, particularly in response to cold exposure. In addition to the constitutive BAT depots present at birth, BAT cells can be induced within WAT depots under specific metabolic and climatic conditions. These cells, called inducible brown fat, “brite,” or beige fat, are currently the focus of intense investigation as a possible treatment for obesity. Inducible brown fat is associated with higher bone mineral density, suggesting that brown fat interacts with bone growth in previously unrecognized ways. Finally, BAT may have contributed to climatic adaptation in hominins. Here, I review current findings on the role of BAT in thermoregulation, bone growth, and metabolism, describe the potential role of BAT in moderating the obesity epidemic, and outline possible functions of BAT across hominin evolutionary history. Yrbk Phys Anthropol 156:98–115, 2015. © 2014 American Association of Physical Anthropologists Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/110636/1/ajpa22661.pdf